Family worship - Whitney, Donald S. (Professor) (Wheaton, Illinois : Crossway, 2016)
Many Christian families have never experienced the joy and spiritual benefits of family worship—a practice rooted in history but largely neglected in our day. In this down-to-earth book, Donald Whitney offers parents a practical guide for leading their families in daily worship, walking readers through three crucial elements: reading Scripture, praying together, and singing songs in praise of God’s name. He then responds to common “What if?” scenarios, such as “What if the father is not a Christian?” and “What if the children are very young?” Looking to the Bible and church history, this guidebook promises to help parents establish a pattern of daily, God-honoring, spiritually uplifting worship in their homes.
"As for me and my house, we will serve the Lord," family worship in the Bible -- "Here the reformation must begin," family worship in church history -- "Read, pray, and sing," the elements of family worship -- "No family worship situation is unique," but what if ... ? -- "Isn't this what you really want to do?" -start today.
Includes bibliographical references (pages 71-75) and index.
Keywords: Families -- Religious life; Worship